POLA KOMUNIKASI KELUARGA DENGAN PERILAKU SEKSUAL BERISIKO PADA REMAJA TUNARUNGU DI SEKOLAH LUAR BIASA KECAMATAN PATRANG KABUPATEN JEMBER - Livia Dwi Ramadhani; Tantut Susanto; Latifa Aini Susumaningrum (Jurnal Kesehatan Reproduksi, 2019)
Abstract Background: Deaf adolescent during their development needs special attention particularly parents, to prevent risk for sexual behavior. Risk for sexual behavior among deaf adolescent related to the role of parents can be facilitated by families on how families communicate issues regarding reproductive health of deaf adolescents. Objective: The purpose of this study was to analyze the relationship between the family communication patterns and risky sexual behavior in Disabled Children School, Patrang regency of Jember district Method: A cross-sectional study was conducted among 53 deaf adolescent aged 11-20 with convenience sampling. A questionnaire was used to identify the sociodemography of participants while the data family communication patterns of was obtained by using the Family Communication Patterns Questionnaire and Adolescents Reproductive Health (ARH) Questionnaire to measure risky sexual behavior. Spearman test was performed to analyze the objective of the study. Results: There is a correlation between family communication patterns and risky sexual behavior in Disabled Children School, Patrang regency of Jember district (r = -0,301; p-value= 0,029). Conclussion: Family communication patterns received by deaf adolescents determine their sexual behavior. Deaf adolescents with dysfunctional family communication patterns tend to show risky sexual behavior. Keywords: family communication pattern, risk for sexual behavior, deaf adolescents Abstrak Latar belakang: Remaja tunarungu selama tumbuh kembangnya membutuhkan perhatian khusus terutama orang tua, untuk mencegah perilaku seksual berisiko. Perilaku seksual berisiko di kalangan remaja tunarungu berkaitan dengan peran orang tua dan dapat difasilitasi oleh keluarga terkait bagaimana keluarga mengkomunikasikan masalah kesehatan reproduksi remaja tunarungu. Tujuan: Mengetahui hubungan antara pola komunikasi keluarga dengan perilaku seksual berisiko pada remaja tunarungu di Sekolah Luar Biasa Kecamatan Patrang Kabupaten Jember. Metode: Desain penelitian yang digunakan adalah cross-sectional dilakukan pada 53 remaja tunarungu berusia 11-20 tahun dengan convenience sampling. Instrumen menggunakan kuesioner Pola Komunikasi Keluarga dan Kuesioner Adolescents Reproductive Health (ARH) untuk mengukur perilaku seksual berisiko. Hasil: Ada hubungan antara pola komunikasi keluarga dengan perilaku seksual berisiko pada remaja tunarungu di Sekolah Luar Biasa Kecamatan Patrang Kabupaten Jember (r = -0,301; p-value= 0,029). Kesimpulan: Pola komunikasi keluarga yang diterima oleh remaja tunarungu menentukan perilaku seksualnya. Remaja tunarungu dengan pola komunikasi keluarga disfungsional cenderung menunjukan perilaku seksual yang berisiko. Kata kunci: pola komunikasi keluarga, perilaku seksual berisiko, remaja tunarungu